Nonlinear association between glycated hemoglobin levels and mortality in elderly patients with non-diabetic chronic kidney disease: a national health and nutrition examination survey analysis - Huang, Lihua; He, Liuliu; Zeng, Qingfeng; Huang, Jinjing; Luo, Xiaoyan; Zhong, Qiuming (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between glycated hemoglobin (HbA1c) levels and mortality outcomes in elderly patients with non-diabetic chronic kidney disease (CKD) has not been well characterized. This study aimed to investigate the correlation between HbA1c levels and all-cause and cardiovascular disease (CVD) mortality in elderly individuals with non-diabetic CKD.MethodsData from the NHANES (1999-2018) were analyzed to measure HbA1c levels in whole blood using high-performance liquid chromatography (HPLC). Information on deaths and subsequent details was collected through the National Mortality Index until December 31, 2019. Hazard ratios (HR) and 95% confidence intervals (CIs) for all-cause and CVD mortality were calculated using weighted Cox proportional hazards and restricted cubic spline models.ResultsAmong the 1,931 participants (mean [SE] age, 73.2 [0.2] years; 61.9% female), over a median follow-up period of 7.6 years, a total of 1,003 deaths were observed, including 412 from CVD. HbA1c was divided into four quartiles: Quartile 1 (3.7–5.3%), Quartile 2 (5.4–5.6%), Quartile 3 (5.7–5.8%) as the reference group, and Quartile 4 (5.9–6.4%). Higher risks of all-cause mortality were noted in the lowest and highest HbA1c quartiles, with adjusted HR (95% CI) of 1.48 (1.18–1.87) and 1.31 (1.01–1.70) respectively. For CVD mortality, the lowest quartile showed a significantly increased risk (HR 1.94, 95% CI: 1.29–2.90), but the highest quartile did not significantly differ from the reference, with HR 1.14 (0.73–1.77). The RCS analysis indicated a U-shaped nonlinear relationship between HbA1c levels and all-cause mortality (P = 0.026 for nonlinearity) and a J-shaped nonlinear relationship with CVD mortality (P = 0.035 for nonlinearity).ConclusionThis cohort study suggests that both low and high HbA1c levels are associated with an increased risk of all-cause mortality in elderly patients with non-diabetic CKD.